Survey of the side effects of most commonly administered covid-19 vaccines in population of Lahore - Khudija Amna Arif; Sheraz, Marriam; Zia Ul Hassan; Khushbakht Sana; Umaira Anjum; Naif Usman Saigol (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVES: In December 2019, a virus, COVID-19, was identified in China, causing respiratory symptoms. Due to its contagious nature, it spread worldwide, and in 2020, the WHO declared the pandemic. The most effective way to deal with this situation was to develop vaccines, so various vaccines were developed in a short period of time. This causes the spread of various myths and misconceptions about its safety and side effects. The main objective of our study is to observe the side effects of various Covid vaccines. METHODOLOGY: A cross-sectional survey of 727 vaccinated individuals of age above 12 years from Lahore selected via convenient sampling was done between Oct 2022 to March 2023 by filling out the Google form and taking verbal interviews from Primary Health Care teaching center Nainsukh, Sadat Clinic Harbanspura and online questionnaire after gaining IRB approval number FMH-16/05/2022-IRB-1054). RESULTS: The majority of the respondents received the Sinovac vaccine, followed by Sinopharm AstraZeneca/Oxford and Pfizer-BioNTech. People receiving mRNA have more side effects than people receiving other vaccines. A wide range of symptoms was observed. 64.8% of them report pain at the injection site (p=0.00), while 57% report fever (P=0.00). Most of the symptoms range from mild to moderate intensity, and a minimal number of people require treatment for them. CONCLUSION: Covid vaccine is generally safe and has mild to moderate intensity side effects.